A comparison of two instructional strategies to enhance critical thinking ability of high school freshmen - Nuestro, Ma. Agnes P. (2004)
Using a quasi-experimental design, two instructional strategies were compared in terms of their effects on critical thinking ability related to vegetables of freshmen in Dasmariñas National High School (DNHS), Cavite. Direct instruction or didactic teaching is a teacher-centered strategy with teachers as major information providers. Critical thinking instruction, on the other hand, is a student-centered strategy that encourages students to develop the ability to reasonably reflectively go about deciding what to believe or do. The direct instruction techniques used were lecture, recitation and demonstration while the critical thinking instruction techniques used were concept mapping, action maze, debate, role playing and journal writing. The random method was used to select the school of two freshmen classes, and to assign a class to either strategy, and topics to specific instructional techniques in the two groups. The intervention consisted of seven one-hour sessions given during a period of one month by the same teacher. The topics for the sessions were drawn from the students' responses to a questionnaire on vegetable-related experiences. Based on the t-test using mean pretest and posttest scores in a Critical Thinking Ability Test on Vegetables, both instructional strategies were found to have significantly increased critical thinking ability, in general, and in each of the following four aspects: elementary classification, basic support, inference and advanced clarification. However, the direct instruction group had significantly higher gain scores in elementary classification and basic support while the critical thinking instruction group had significantly higher gain scores in inference and advanced clarification. The difference may not be all attributable to the instructional strategy since the two groups differed in terms of entry grade in high school and average pretest score in inference. They did not differ in terms of mental ability, nutritional status, vegetable-related experiences and initial critical thinking ability, in general, and in each of the three aspects: elementary clarification, basic suport and advanced clarification.